Model based on the Lean Manufacturing methodology to increase the OTIF of a MYPE company in the textile sector - Bryan, Anzualdo (2023)
Textile companies in Peru are currently facing problems of low productivity and exports, caused by the COVID-19 pandemic, generating a deficit in the trade balance and forcing producers to be more competitive. Reason why the national industry seeks to raise the standards of delivering products on time and fully delivering orders, increasing the level of service offered. For this reason, an improvement model is proposed for its application in the printing area of a Peruvian MYPE textile company, which will seek to improve production times and reduce reprocessing in order to increase the company's OTIF. Finally, the validation will be carried out through simulation to rein in the viability of the improvement model in the textile company and to validate the effectiveness of the proposed tools to solve the existing problems in the printing area.